Analysis of computer textbooks content for intermediate stage according to the theory of multiple intelligence (Journal Of Educational and Psychological Researches, 2018)
The purpose of current study is to analyze the computer textbooks content for intermediate stage in Iraq according to the theory of multiple intelligence. By answering the following question “what is the percentage of availability of multiple intelligence in the content of the computer textbooks on intermediate stage (grade I, II) for the academic year (2017-2018)? The researcher followed the descriptive analytical research approach (content analysis), and adopted an explicit idea for registration. The research tool was prepared according the Gardner’s classification of multiple intelligence. It has proven validity and reliability. The study found the percentage of multiple intelligence in the content of computer textbooks for the intermediate stages (grade I, II) separately (40%), (59%) respectively, collectively (66.67%).